Effective root depth and water uptake ability of winter wheat by using water stable isotopes in the Loess Plateau of China - Bing, Wang; Lijian, Zheng; Juanjuan, Ma; Xihuan, Sun; Xianghong, Guo; Fei, Guo (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: A field experiment using PVC growth tubes was conducted in the Loess Plateau of China to determine the effective root depth (ERD) of winter wheat and its relationship with root distributions and soil water conditions. The water stable isotopes technique was used to estimate the water uptake contributions of different root depths during the growth stages. On the basis of IsoSource and the Romero-Saltos model, the ERD was 0-40 cm in the majority of the growth stage. However, in the heading and filling stages, the ERD could reach 60%-75% of the maximum root depth. Furthermore, the contributions to water uptake of different root depths were correlated with variations in soil water and root length density (r=0.395 and 0.368, respectively; p0.05). However, by path analysis, the low decisive coefficient indicated that root distribution and soil water content did not always follow the same trend as water uptake. The conclusions of this study can help with understanding winter wheat water uptake mechanisms in arid and semi-arid regions and increasing water use efficiency.Keywords: effective root depth, water stable isotopes, water uptake, root distribution, soil water contentDOI: 10.3965/j.ijabe.20160906.2450Citation: Wang B, Zheng L J, Ma J J, Sun X H, Guo X H, Guo F. Effective root depth and water uptake ability of winter wheat by using water stable isotopes in the Loess Plateau of China. Int J Agric & Biol Eng, 2016; 9(6): 27－35.